Mechanical overloading promotes chondrocyte senescence and osteoarthritis development through downregulating FBXW7. Issue 5 (20th January 2022) - Zhang, Haiyan; Shao, Yan; Yao, Zihao; Liu, Liangliang; Zhang, Hongbo; Yin, Jianbin; Xie, Haoyu; Li, Kai; Lai, Pinglin; Zeng, Hua; Xiao, Guozhi; Zeng, Chun; et al.
Abstract : Objectives: To investigate the role of mechanical stress in cartilage ageing and identify the mechanistic association during osteoarthritis (OA) progression. Methods: F-box and WD repeat domain containing 7 (FBXW7) ubiquitin ligase expression and chondrocyte senescence were examined in vitro, in experimental OA mice and in human OA cartilage. Mice with Fbxw7 knockout in chondrocytes were generated and adenovirus-expressing Fbxw7 (AAV-Fbxw7) was injected intra-articularly in mice. Destabilised medial meniscus surgery was performed to induce OA. Cartilage damage was measured using the Osteoarthritis Research Society International score and the changes in chondrocyte senescence were determined. mRNA sequencing was performed in articular cartilage from Fbxw7 knockout and control mice. Results: Mechanical overloading accelerated senescence in cultured chondrocytes and in mice articular cartilage. FBXW7 was downregulated by mechanical overloading in primary chondrocytes and mice cartilage, and decreased in the cartilage of patients with OA, aged mice and OA mice. FBXW7 deletion in chondrocytes induced chondrocyte senescence and accelerated cartilage catabolism in mice, as manifested by an upregulation of p16 INK4A, p21 and Colx and downregulation of Col2a1 and ACAN, which resulted in the exacerbation of OA. By contrast, intra-articular injection of adenovirus expressing Fbxw7 alleviated OA in mice. Mechanistically, mechanical overloading decreased Fbxw7 mRNA transcription and FBXW7-mediated MKK7 degradation, which consequently stimulated JNK signalling. In particular, inhibition of JNK activity by DTP3, a MKK7 inhibitor, ameliorated chondrocyte senescence and cartilage degeneration Conclusions: FBXW7 is a key factor in the association between mechanical overloading and chondrocyte senescence and cartilage ageing in the pathology of OA.